Studies of Earthquake Energies in Taiwan: A Review - Jeen-Hwa Wang (Terrestrial, Atmospheric and Oceanic Sciences, 2016)
This paper reviews studies on earthquake energies, seismic efficiency, radiation efficiency, scaled energy and energy-magnitude law conducted by Taiwan seismologists and foreigners who used seismic data from Taiwan to study these problems. Sufficient seismic and geodetic data permits energy measurements from the 20 September 1999 Ms 7.6 Chi-Chi earthquake and its larger-sized aftershocks. The results provide significant information on earthquake physics. The issues in this review paper include measures of these physical quantities and related theoretical or analytical studies of these physical quantities made by both Taiwan’s seismologists and foreigners who used seismic data of Taiwan to study related problems.